Space Boy - Book 3 Volume 3 - McCranie, Stephen 1987- (Milwaukie, OR : Dark Horse Books, 2019)
"Amy lives on a colony in deep space, but when her father loses his job the family moves back to Earth, where she has to adapt to heavier gravity, a new school, and a strange boy with no flavor." --From the publisher.
"This book collects Space Boy episodes 33-48, previously published online at WebToons.com" --Title page verso.
Keywords: Moving, Household -- Comic books, strips, etc; Self-perception -- Comic books, strips, etc; Friendship in children -- Comic books, strips, etc; Comic books, strips, etc; Science fiction